2015
DOI: 10.1016/j.energy.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of R-1234ze(Z) as drop-in replacement for R-245fa in Organic Rankine Cycles – From thermophysical properties to cycle performance

Abstract: a b s t r a c tTo Prof. Jürgen K€ ohler to his 60th birthday.ORCs (Organic Rankine Cycle) experience growing interest for the generation of electricity from industrial waste heat. However, the widely used working fluid R-245fa does not seem to be sustainable due to its relative high GWP (Global Warming Potential) of almost 900 [1]. In this work, we have evaluated the low GWP working fluid R-1234ze(Z) as drop-in replacement for R-245fa in low-grade ORC processes. Our studies thereby comprise a comparison of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 18 publications
1
20
0
3
Order By: Relevance
“…In spite of a wide range of working fluids has been studied by many researchers, only few different working fluids are applied to commercial ORC systems. A non-exhaustive list of the main ORC manufacturers and the working fluids was listed in [26], working fluid R245fa is founded to be the most common used working fluid for various heat resources including low-temperature geothermal brine. Due to the relative high global warming potential of working fluid R245fa, the replacement of R245fa by new working fluids with low GWP has rising a growing interest.…”
Section: Working Fluid Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a wide range of working fluids has been studied by many researchers, only few different working fluids are applied to commercial ORC systems. A non-exhaustive list of the main ORC manufacturers and the working fluids was listed in [26], working fluid R245fa is founded to be the most common used working fluid for various heat resources including low-temperature geothermal brine. Due to the relative high global warming potential of working fluid R245fa, the replacement of R245fa by new working fluids with low GWP has rising a growing interest.…”
Section: Working Fluid Candidatesmentioning
confidence: 99%
“…Due to the relative high global warming potential of working fluid R245fa, the replacement of R245fa by new working fluids with low GWP has rising a growing interest. The replacement of R245fa with R1234ze(Z) was technically evaluated for the low-grade heat source at the temperature range of 373.15-523.15 K [26]. In present work, three candidate organic fluids R245fa, R1234ze(Z), and R1234ze(E) are selected, based on the guidelines of working fluid selection already discussed and the use of low GWP working fluids.…”
Section: Working Fluid Candidatesmentioning
confidence: 99%
“…The safety measures needed on board are far more comprehensive for highly flammable fluids, such as cyclopropane, although not insurmountable; for example, methane is routinely used as a fuel on large ships. In addition, as Petr et al [36] found in a recent study, R1234ze(z) has in ORC applications lower viscosities and similar thermal conductivities compared to R245fa, thus having potentially better heat transfer characteristics. A study by Longo et al [37] confirms this in an experimental study, finding that R1234ze(z) has much higher heat transfer coefficients than other alternatives in high temperature heat pump applications.…”
Section: Discussionmentioning
confidence: 88%
“…Longo等人 [10,11] 给出了类似的结论, 他们发现, R1234ze(Z)的换热系数比现在常用的制冷剂大得多, 但是其摩擦压降与R600a类似. Fukuda等人 [12] 、Petr 和Raabe [13] Table 1 The experimental saturation pressure of R1234ze(Z) obtained by low temperature setup Table 2 The experimental saturation pressure of R1234ze(Z) obtained by high temperature setup Antoine 方 程 , Wagner 方 程 以 及 亥 姆 霍 兹 方 程 形 式 如下:…”
unclassified